Teachers' perceptions of Merdeka curriculum development in Nias - Anjelina Agustina Ndruru (Universitas Palan, 2024)
This research aims to explore teachers' perceptions of the development of the Merdeka Curriculum on Nias Island. Using a qualitative approach, data was collected through in-depth interviews with a number of teachers in schools on Nias Island. Thematic analysis was used to identify patterns and key themes that emerged from conversations with teachers. The results of the study highlighted the different views, challenges and expectations of teachers regarding the implementation of the Merdeka Curriculum. The findings provide valuable insights into how educators in the region are responding to and managing the dynamics of the development of the new curriculum. The implications of the findings of this study are expected to provide guidance for improving the implementation of the Merdeka Curriculum in Nias Island and similar areas.